NILAI-NILAI GOTONG ROYONG PADA TRADISI BAHAUL DALAM MASYARAKAT BANJAR DI DESA ANDHIKA SEBAGAI SUMBER PEMBELAJARAN IPS - Subiyakto, Bambang; Syaharuddin, Syaharuddin; Rahman, Gazali (Vidya Karya, 2016)
Abstract:Â The purpose of this research is to describe the values of gotong royong in Banjarese society in Andhika village that has âa bahaulâ tradition. Thus, the values of gotong royong have significance to social studies education as the learning source. This research used the qualitative approach, which the data collection were through interview, observation, and document study. The data was analized by using data reduction, display the data and verification or conclusions. The data verification is through these following steps, namely, extended observation, triangulation, and discussion with the colleagues. The results of the study show the values of Gotong royong in bahaul tradition are seen in these activities; taturukan, pangayuan, pangawahan, and lalawatan. The activities have a significant impact in Social Studies Education. The significant impact could be seen on the values in âbahaulâ such as solidarity, tolerance and caring to a society. Thus, this study is able to enrich the source of Social Studies Education in the school.Â Keywords: Â Â Â Â Gotong royong, bahaul tradition, banjarese society, social studies education.Â Abstrak: Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai gotong royong dalam masyarakat Banjar di desa Andhika pada acara bahaul dan signifikansinya dalam pembelajaran IPS di sekolah sebagai sumber belajar. Penelitian menggunakan pendekatan kualitatif dengan pengumpulan data melalui wawancara, observasi dan studi dokumen. Data dianalisis melalui reduksi data, penyajian data danÂ verifikasi/kesimpulan. Keabsahan data melalui perpanjangan waktu pengamatan,Â triangulasi, dan cek-cek anggota. Hasil penelitian menunjukkan bahwa gotong royong dalam bahaul tampak pada aktivitas taturukan, pangayuan, pangawahan dan lalawatan. Aktivitas tersebut memiliki signifikansi dalam pendidikan IPS karena aktivitas bahaul memiliki nilai solidaritas, toleransi, dan peduli sosial sehingga memperkaya sumber belajar IPS di sekolah.Â Kata-kata Kunci: gotong royong, bahaul, masyarakat Banjar dan Pendidikan IPS